25-year trajectories of physical activity and atrial fibrillation risk: results from the ARIC study - Wang, Tongxin; Wang, Xinyi; Zhang, Tao; Zhang, Jie; Lai, Runmin; Zhang, Jiqian; Ma, Dan; Jia, Yan; Liu, Qiyu; Li, Qiuyi; Jia, Jundi; Tian, Wende; et al. (Frontiers in Cardiovascular Medicine, 2024)
BackgroundThe relationship between serial changes in physical activity and the risk of developing atrial fibrillation (AF) has been rarely studied.ObjectivesTo evaluate the association between changes in physical activity over time and the incidence of AF.MethodsA total of 11,828 participants without AF at baseline (visit 1: 1987–1989) from the ARIC Study were included. Physical activity was measured using the modified Baecke Physical Activity Questionnaire at three different visits between 1987 and 2013. Physical activity trajectories over 25 years were identified using latent class trajectory modeling. The primary outcome was the incidence of AF. Multivariable Cox hazard regression models were used to evaluate the relationship between physical activity trajectories and the incidence of AF.ResultsOver a median follow-up of 24 years, 2,108 AF cases (17.8%) occurred. Four distinct physical activity trajectories were identified: light [n = 5,266 (43.3%)]; reduced moderate [n = 3,583 (29.0%)]; moderate [n = 2,691 (25.0%)]; and vigorous intensity [n = 288 (2.8%)]. Compared to the light group, the hazard ratio (HR) and 95% confidence interval (CI) for AF were 1.18 (1.07–1.30) (p < 0.001) for the reduced moderate group, 0.61 (0.53–0.70) (p < 0.001) for the moderate group, and 0.82 (0.59–1.12) (p = 0.21) for the vigorous group, after multivariate adjustments.ConclusionMaintaining moderate levels of physical activity is associated with a lower risk of AF, while a decrease in activity from moderate to light levels increases the risk. These findings highlight the importance of sustaining adequate physical activity levels for the prevention of AF.